2018
DOI: 10.7575/aiac.alls.v.9n.1p.5
|View full text |Cite
|
Sign up to set email alerts
|

A Flipped Writing Classroom: Effects on EFL Learners’ Argumentative Essays

Abstract: According to the literature, flipped teaching is a relatively new pedagogical approach in which the typical activities of classroom lectures followed by homework in common teaching practice are reversed in order, and most often integrated or supplemented with some types of instructional materials, such as instructional videos or PowerPoint files. This experimental study, using a pre-test-treatment-posttest-delayed posttest design, was aimed at investigating the effect of flipped instruction on Iranian EFL lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
2
26
0
4
Order By: Relevance
“…The use of technology can attract students' attention and curiosity. The benefits of using the Flipped Classroom strategy in facilitating learning activities and improving students' achievement has also been proven in studies conducted by Zakiya (2020), Soltanpour & Valizadeh (2018), Afriyalsanti et al (2016), and Engin (2014). To support the technology-integrated learning process using the Flipped Classroom strategy, this study utilized a web-based interactive learning media called Edpuzzle.…”
Section: Introductionmentioning
confidence: 83%
“…The use of technology can attract students' attention and curiosity. The benefits of using the Flipped Classroom strategy in facilitating learning activities and improving students' achievement has also been proven in studies conducted by Zakiya (2020), Soltanpour & Valizadeh (2018), Afriyalsanti et al (2016), and Engin (2014). To support the technology-integrated learning process using the Flipped Classroom strategy, this study utilized a web-based interactive learning media called Edpuzzle.…”
Section: Introductionmentioning
confidence: 83%
“…Literatürde TYES'in yazma başarısını arttırdığı sonucuna ulaşılan birçok çalışma bulunmaktadır (Baranovic, 2013;Leis, Tohei ve Cooke, 2015;Özbilen, 2018;Özdemir, 2017;Pavanelli, 2018;Soltanpour ve Valizadeh, 2018). Bu çalışmalardan birinde Özdemir (2017) TYES'in Türkçe öğretmeni adaylarının öyküleyici ve bilgilendirici metin yazma becerilerini geliştiren, içerik oluşturma ve yazma süreçlerini düzenlemeye katkı sağlayan bir model olduğu sonucuna varmıştır.…”
Section: Tyes'in Yazma Başarısına Etkisiunclassified
“…Bunun yanı sıra Pavanelli (2018) tarafından yapılan çalışma TYES'in akademik yazma performansı üzerinde anlamlı etkisinin olduğunu; öğrencilerin TYES modelini etkileşime ve iş birliğine imkân tanıyan, yazma becerilerini geliştirmede geleneksel yöntemlere göre daha etkili olan bir öğrenme kaynağı olarak algıladıklarını göstermiştir. Başka bir çalışmada Soltanpour ve Valizadeh (2018) TYES'in tartışmacı metin yazma becerisini geleneksel yöntemlere göre daha fazla geliştirdiğini, TYES ve geleneksel sınıftaki öğrencilerin başarıları arasındaki anlamlı farkın zaman içerisinde değişmediğini ortaya koymuşlardır. Lisans öğrencileriyle yaptığı atölye çalışmasında TYES'in yazma becerisi üzerinde etkili olduğu sonucuna varan Baranovic (2013) TYES'le öğrencilerin yazma konularını daha kısa zamanda öğrenebildiklerini tespit etmiştir.…”
Section: Tyes'in Yazma Başarısına Etkisiunclassified
See 1 more Smart Citation
“…They applied flipped classrooms in teaching English writing and found that flipped instruction had a positive impact on students' writing and their overall academic performance. Similarly, Soltanpour and Valizadeh (2018) investigated the effect of flipped classrooms on Iranian EFL learners' quality in argumentative essays. When compared with a control group, students in the FC outperformed the traditional class, both directly after the flipped instruction occurred, and again after time had passed in a second comparison.…”
Section: Skills Improvement: Writingmentioning
confidence: 99%